Practical reliability engineering - O'Connor, Patrick D. T.; Kleyner, Andre (Wiley, 2012)
"Maintaining the academic and practical level of the Fourth Edition, while keeping up with modern reliability practices as evolve, this new edition presents the latest reliability software packages; has an expanded section on Weibull distribution, the most commonly used distribution in reliability mathematics; and includes PowerPoint slides and solutions for course tutors held on a companion website. It is an essential text for experienced design and reliability engineers, as well as engineers studying for CRE, ASQ or IQA certification and graduate or senior undergraduate students in quality assurance or reliability"--